Pronomina Penunjuk Tempat dalam Bahasa Bima Desa Tonda Kecamatan Madapangga - Desi Rachmawati; Syamsinas Jafar (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2020)
This study aims to describe the form of pronouns in the Bima language, Tonda village, Madapangga sub-district, Bima district. Data collection in the study used the observation method, the interview method, and the introspection method. While the data analyst uses the intralingual equivalent method which will compare two different languages. The results of this study found three forms of place-indicating pronouns in the Bima language, namely ta ake 'here', ta ede 'there', and ta aka 'there'. The pronoun ta ake 'here' is used to indicate a close distance, ta ede 'there' is used to refer to a distance away while ta aka 'there' is used to indicate a far distance. In addition to the form of the pronouns indicating the place, there is also the form of the pronouns that indicate the place markers for the particles re and ku as an affirmation. It was also found that the syntactical pronouns indicating the place were distributed, namely the distribution of the beginning of the sentence, the distribution of the middle of the sentence, and the distribution of the end of the sentence and the syntactic behavior of the place-marking pronouns, namely, prepositions to and from which were seen based on antasaden.